Impact of osteonecrosis of the jaw on osteoporosis management: executive summary of an ESCEO and Foundation for Research on Osteoporosis and other Bone Diseases Working Group Meeting. (December 2007) - Rizzoli, Renéé; Burlet, Nansa; Cahall, David; Delmas, Pierre D; Eriksen, Erik Fink; Felsenberg, Dieter; Grbic, John; Jontell, Mats; Landesberg, Regina; Laslop, Andrea; Matton, Peter; Papapoulos, Socrates; et al.
The first reports of osteonecrosis of the jaw in patients taking bisphosphonates to reduce excessive bone resorption were published in 2003. Subsequent reports raised concern and resulted in manufacturers writing letters of caution to physicians and dentists. Recommendations were issued by the US FDA, and the European Agency for the Evaluation of Medicinal Products requested that pharmaceutical companies update their product information and package leaflets. The European Society on Clinical and Economic Aspects of Osteoporosis and Osteoarthritis and the Foundation for Research on Osteoporosis and other Bone Diseases Working Group Meeting was convened on 14 December 2006 in Geneva, Switzerland, to review the available data and published guidelines on this rare but serious condition. The purpose of the meeting was to assess the impact of osteonecrosis of the jaw on the management of osteoporosis. The discussion focused on the current definition of osteonecrosis of the jaw, its epidemiology and pathophysiology, as well as identifying potential risk factors. Agreement was also reached on best practice in terms of diagnosis and management.